Pengembangan E-Modul Berbasis Socio Scientific Inquiry Based Learning (SSIBL) pada Materi Sistem Pencernaan - Safitri Safitri; Miza Nina Adlini (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to develop a Socio Scientific Inquiry Based Learning (SSIBL)-based e-module on the digestive system topic that is valid, practical, and effective for use in biology learning. The method used was Research and Development (R&D) employing the 4D model, which includes the stages of define, design, develop, and disseminate. The research subjects consisted of 30 students from grade XI Science at a private Islamic senior high school (Madrasah Aliyah Swasta) and one biology teacher. The research instruments included validation sheets, teacher and student response questionnaires, and learning achievement tests. The results showed that the e-module was highly valid with a percentage of 95.83% (content) and 91.67% (media). Teacher responses reached 98.07%, and student responses reached 93.80%, both categorized as very practical. The effectiveness test obtained a score of 0.71, classified as high, indicating that the e-module was effective in improving students’ learning outcomes. In conclusion, the SSIBL-base e-module is feasible to be used as an alternative digital teaching material for the digestive system topic. This e-module not only facilitates students’ understanding of biology but also enhances their awareness of health issues and their ability to make wise decisions in everyday life.   Keywords: Biology, E-Module, Learning Outcomes, SSIBL, Digestive System.